Adoption of body cameras by United States police angencies: an organisational analysis - Nowacki, Jeffrey S. (Policing and society, 2018)
In the wake of recent high-profile lethal force incidents in the United States, police agencies have felt pressure to mandate that officers wear cameras to video record encounters with citizens. In this article, we examine how organisational characteristics influence the adoption of body-worn camera (BWC) technology in American police agencies. Using data from the 2013 Law Enforcement Management and Administrative Survey (LEMAS), we conduct logistic regression analysis to examine how various organisational variables influence whether agencies use BWCs. We analyse responses from 823 agencies. Our results suggest that departments that utilise more technology are more likely to adopt further innovations, such as BWCs. Conversely, we find that agencies with large operating budgets and agencies represented by collective bargaining units are less likely to report utilising BWCs. Agencies with more bargaining power have more leverage to resist pressures to use technology which might limit police discretion.